Poison princess - Cole, Kresley (London : Simon & Schuster, 2012)
In the aftermath of a cataclysmic event, sixteen-year-old Evie, from a well-to-do Louisiana family, learns that her terrible visions are actually prophecies and that there are others like hersel f-- embodiments of Tarot cards destined to engage in an epic battle.
Keywords: Ability -- Juvenile fiction; Prophecies -- Juvenile fiction; Tarot -- Juvenile fiction; Supernatural -- Fiction